(untitled) (Kyiv-Mohyla Law and Politics Journal, 2021)
The growing interest in alternative forms of dispute resolution has prompted attention to the peculiarities of the application of the principles of publicity and confidentiality in the arbitration. It is determined that the observance of the principle of publicity of the legal proceeding is the basis for ensuring justice. However, approaches to the application of this principle in arbitration differ both from the point of view of researchers and within the framework of legal regulation at the national and international levels. Some believe that the application of the principle of publicity will destroy the features of arbitration as such. However, the presented article demonstrates other approaches. The position was supported that the principle of confidentiality should be distinguished from the concepts of “privacy” or “closed trial”. In this context, publicity is often compared to concepts such as “openness”, “clarity” and “transparency” of the proceedings. Of concern is some regulatory restriction on the application of the principle of publicity, which affects the level of awareness of the activities of arbitration courts among the public and lawyers who intend to use alternative forms of dispute resolution. It is hoped that such further research will help solve similar problems.